THE INFLUENCE OF STUDENTS' WRITING SKILL BY WRITING DIARY IN RECOUNT TEXT FOR JUNIOR HIGH SCHOOL STUDENTS - MAS DARUL IHSAN; DJOKO ARDHITYAWAN (Fakultas Sastra Universitas Gresik, 2016)
The focus of learning English as an ESL student is able to communicate in English. The communicated competence refers to listening, speaking, reading and writing. Based on the other research, as an ESL student, writing is often considered a difficult English skill. Some techniques are needed by a teacher to solve the writing difficulties. One of the problem solving is writing a diary. Additionally, students often make a mistake in writing. Therefore, this research was to know whether there is a significant influence on students' writing skill by writing a diary in recount text for junior high school students. The method of this research was a quasi-experimental method which is the treatment held in several meetings as they need and eighty minutes for each meeting. In collecting the data, the researcher used the instrument in written test questions. After tried out, the instrument was used for the pre-test and post-test. Pre-test used to find out students’ writing ability before treatment. Then post-test used to find out students’ writing ability after treatment, then the researcher analyzed the data. The population of this research was students volunteer in eighth grade, which consisted of 20 students. The sample taken from the announcement in social media, it means that the researcher makes an announcement for the teacher who wants their students to be selected as a sample in this research. It was taken by using randomly that is cluster random sampling technique.Based on the data analysis, it was found that the result is the students’ writing skill had significant influence. The conclusion of this research is writing a diary was effective to influence the students’ writing skill. It is clear that there is any significant influence of using writing diary technique towards students’ writing skill. It is better to use this technique in teaching writing for the teachers and other readers because this technique is interesting and enjoyable when it is applied.